From The History of The Jadidist Movement in The Emirate of Bukhara - Hazratkulov Kamal Ishonkulovich (Web of Journals Publishing, 2023)
The article discusses the emergence of Jadidism in the Bukhara Emirate at the beginning of the last century and the historical conditions at that time. Teaching methods in schools opened in the emirate are explained on the basis of historical facts.
Keywords: Bukhara, national liberation, education. Society newspaper.